Peaked density profiles due to neon injection on FTU. (23rd June 2015) - Mazzotta, C.; Bañón Navarro, A.; Gabellieri, L.; Marinucci, M.; Pucella, G.; Told, D.; Tudisco, O; Apruzzese, G.; Artaserse, G.; Sozzi, C.
Abstract: Neon injection in FTU can cause a spontaneous increase of the line-average density by a factor 2. The recent experiments were devoted to characterize the plasma response to the neon injection at different densities and plasma currents. A qualitative estimate from UV spectroscopy measurements indicates that the density behaviour cannot be attributed simply to the stripped electrons from the puffed impurity, but a modification of particle transport should be invoked in order to explain the spontaneous rise and the higher peaking. JETTO transport and GENE gyrokinetic codes analyses, as well as a calculation of the electron diffusion coefficients D and pinch velocity U, contribute to feature the peaking effect.